An Early Ordovician (Floian) asterozoan (Echinodermata) of problematic class-level affinities. (March 2020) - Blake, Daniel B.; Gahn, Forest J.; Guensburg, Thomas E.
Abstract: Falloaster anquiroisitus new genus new species (Asterozoa, Echinodermata) is described from the Floian (Early Ordovician) Garden City Formation of Idaho. The new taxon is known from a single small specimen. Because of weathering, remaining disk elements are incomplete. Dorsal surfaces of the ambulacral ossicles of two arms are available, one well preserved, whereas those of a third arm expose the ambulacrals essentially as they would appear in ventral view. Ambulacral ossicles were all but entirely lost on the remaining two arms. Albeit asterozoan, F. anquiroisitus is not assignable at the class level. It is suggestive of the Asteroidea in presence of a domal disk, five abruptly tapering triangular, arched arms, and ambulacral ossicles vaulted to form a furrow. Ambulacral morphology, including the presence of very large podial pores, is unlike that of early asteroids. In addition, no adambulacral or other virgal-series derivatives are present; ambital framework ossicles are absent; a single series of enlarged, plate-like arm ossicles, one series on each side of the arm, come together at the arm midline; and the plate-like series were supported laterally by recurved ambulacral margins. Only remnants of the disk near the periphery survive, these of overall expression unlike any other echinoderm, including asterozoans. The mouth frame is unknown. Falloaster anquiroisitus is argued to represent an extinct lineage apart from the four recognized asterozoan classes, thereby joining a limited number of other problematic early Asterozoa. UUID: http://zoobank.org/a13a5417-44b6-4ac3-90cf-9dc8fb5902bd